PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN RPP KURIKULUM 2013 MELALUI IN HOUSE TRAINING (IHT) OLEH KEPALA SEKOLAH DI SD BUNGKUS KRETEK KABUPATEN BANTUL - Suciati Suciati (Ideguru: Jurnal Karya Ilmiah Guru, 2019)
The purpose of this study were to implemented in-house training to improve the teacher competence in organizing the leson plan of curriculum 2013 in SD Bungkus, Kretek, Bantul, at academic year of 2018/2019. This study used descriptive approach with Kimmis and Taggart design, and conducted in two cycles. The study design was conducted in the following steps: planning, action, observation, and reflection (evaluation). The data collection technique were interview, observation, and discussion. The instrument used in this study were interview sheet, leson plan document and in-house training document. The result of this study reveals there were improvement of teacher competence that determined from evaluation on completeness of the leson plan component in cycle II, compared with those in cycle I. It can be concluded from the study that in-house training may improve teacher competence in organizing the leson plan of curriculum 2013 in SD Bungkus. Keywords: leson plan, in house training.